Computational Study of N-Hexane Extract of Jotang Herba (Acmella uliginosa) - Nabillah, Deya Adiby; Kholifah, Eva; Ahmaddhani, Surya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The study investigates the in silico toxicity of n-hexane extract from Acmella uliginosa (Jotang) herb, a plant widely used in traditional medicine. In silico methods, such as molecular docking, toxicity prediction, and ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) analysis, were employed to assess the potential harmful effects of the extract’s chemical constituents. The primary aim was to evaluate the safety profile of the extract in terms of cytotoxicity, mutagenicity, and organ toxicity. The study used computational tools like Pre.ADMET to predict various toxicological endpoints based on the molecular properties of the compounds identified in the n-hexane extract. The results suggested that while some compounds exhibited low toxicity risk, others showed potential mutagenic or hepatotoxic effects. This in silico approach provides a rapid and cost-effective method for preliminary toxicity assessment, offering valuable insights for further in vivo or clinical studies. The findings underscore the importance of integrating computational techniques into the safety evaluation of herbal medicines.